Invited commentary: dispersal policies, neighborhood disadvantage, and refugee health in a Nordic context - Rostila, Mikael (American journal of epidemiology, 2025)
In this issue of the Journal, Kim et al (Am J Epidemiol 2025;194(3):635-644) examine whether neighborhood disadvantage is associated with cardiovascular disease risk in Denmark. A potential contribution of their article is the study of mediators (cumulative income, unstable employment, and poor mental health) underlying the association using a quasi-experimental design based on a Danish refugee dispersal policy. In this commentary, I draw attention to some potential limitations involving use of refugee dispersal policies as natural experiments. I further discuss the extent to which the mediators studied by Kim et al contribute to our overall understanding of mechanisms linking neighborhood disadvantage and cardiovascular disease risk. However, because a similar dispersal policy was introduced during the same time period in a country neighboring Denmark-Sweden-I also take the opportunity to give an account of the background of dispersal policies in the two countries and offer some general reflections on their consequences for refugee integration and well-being there.